Screening for interaction domain in vault nanocapsules. - Loo, Jonathan Yun Haw. (2013)
Protein nanocapsules are gaining popularity as therapeutic delivery vehicle particularly due to the potential of controlled release kinetics, particularly interesting is pH-controlled molecular release from the protein nanocapsule to release the content in the endosomes. Vault is a naturally assembled hollow protein nanocapsule (75 x 42 x 41 nm3) with a large inner cavity and is mostly composed of major vault proteins (MVP). MVP interacts with C-terminus of vault poly(ADP-ribose)-polymerase (VPARP), namely MVP-minimal interaction domain (mINT) at a domain near the waist of the vault complex in the inner cavity. This interaction between MVP and mINT is important as researches have shown that the mINT may serves as a protein shuttle to load proteins and nanoparticles into the inner cavity of the vault complex as well as the fact that the interaction site is near the waist of the nanocapsule, where the vault opens up under certain conditions. Modifying the interaction site will allow the engineering of non-native pH-dependent interaction functionality onto the vault nanocapsule to open and release its content at specific pH. This project attempted to identify specific domains that are involved in the interactions between MVP and mINT by studying the affinity between MVP domain 3-4 and 4-5 with the mINT. We constructed four plasmids in E. coli expression vector pET-42 b(+) and pET-11a encoding MVP domain 3-4 and 4-5 and mCherry-mINT respectively. These genes were overexpressed to produce protein fractions for validation of interactions. Attempts to over-express GST-MVP45 failed and yielded only GST-tag proteins. Results from affinity test done by running mixture of GST-MVP34 and mCherry-mINT through size exclusion chromatography using Superdex 200 show no or insufficient binding between the two proteins.